You are on page 1of 19

# Chapter 4 Fuzzy projectivity on quotient G-modules

4.1 Introduction
The notion of projectivity of modules was developed by Cartan and Eilemberg [11]. Zahedi and Ameri [57] studied about the fuzzy projectivity and injectivity of modules. Shery Fernandez [45] analysed the fuzzy projectivity of modules. As a continuation of these works, here we introduce the concept of fuzzy projectivity of quotient G-modules. In this chapter we discuss the projectivity and relative projectivity of quotient G-modules and the fuzzy projectivity on it.

87

. Then M is M ∗ -projective if for any G-submodule N ∗ of M ∗ .CHAPTER 4. every homomorphism φ : M → M ∗ /N ∗ can be lifted to a M ψ φ M∗ π M ∗ /N ∗ 4. any homomorphism φ : M → M ∗ /N ∗ can be lifted to a homomorphism ψ : M → M ∗ . where π : M ∗ → M ∗ /N ∗ is the N ∗ of M ∗ . .2. .1 Deﬁnition [45] A G-module M is projective. 88 4.2 Projectivity of G-modules 4. ψ : M → M ∗ such that π ◦ ψ = φ.2 Deﬁnition [45] Let M and M ∗ be G-modules. This means that ∃ a homomorphism canonical homomorphism. if for any G-module M ∗ and any G-submodule homomorphism ψ : M → M ∗ .2. FUZZY PROJECTIVITY ON .

FUZZY PROJECTIVITY ON . then the G-module N and M/N has fuzzy G-modules. Let µ and ν be fuzzy G-modules on M and M ∗ respectively.CHAPTER 4.2. ∀m ∈ M and ψ ∈ Hom(M. Then M is N ∗ -projective and M ∗ /N ∗ -projective. 4. If M has a fuzzy G-module.2. M ∗ ).2.5 Deﬁnition [45] Let M and M ∗ be G-modules. . 4. Then µ is ν -projective if i) M is M ∗ -projective ii) µ(m) ≤ ν (ψ (m)). M ∗ /N ∗ φ M µ ψ π M∗ ν [0.4 Proposition [45] Let M be a G-module and N be a G-submodule of M . 4.3 Proposition [45] 89 Let M and M ∗ be G-modules such that M is M ∗ -projective. Let N ∗ be any G-submodule of M ∗ . . 1] .

CHAPTER 4. 1] Since µ is ν -projective. m ∈ M. . FUZZY PROJECTIVITY ON . ∴ ψ −1 is an anti-weak fuzzy homomorphism of ν onto µ. m ∈ M . ψ ∈ Hom(M.6 Remark 90 Let µ and ν be fuzzy G-modules on M and M ∗ respectively and let µ be m ∈ M .3 Projectivity on fuzzy G-modules Shery [44] formulated the concept of fuzzy G-module projectivity and proved that any ﬁnite dimensional G-module has a fuzzy G-submodules and that completely reducible G-modules have fuzzy completely reducible . . 4. [0. 1] µ(m) ≤ ν (ψ (m)). onto µ. 4. M ∗ ). Then we say that ψ −1 is an anti-weak fuzzy homomorphism of ν M µ ψ M∗ ν M∗ ν ψ −1 µ M ν -projective. [0. M ∗ ) such that µ(m) ≤ ν (ψ (m)).2. ∴ ψ −1 (ν )(m) ≥ µ(m). Hence ∃ ψ ∈ Hom(M.

FUZZY PROJECTIVITY ON . the homomorphism M → M ∗ /N ∗ can be lifted to . 91 G-submodules and derived some of its properties. We analyse the relative projectivity of two quotient G-modules too. then M/N is M ∗ -projective where N is a G-submodule of M . . M g M/N φ f π ψ h M∗ M ∗ /N ∗ Let N be a G-submodule of M and N ∗ be a G-submodule of M ∗ . Here we introduce and analyse the concept of projectivity and fuzzy projectivity on quotient G-modules. Since ψ : M → M ∗ such that π ◦ ψ = φ where π : M ∗ → M ∗ /N ∗ is the canoniM is M ∗ -projective.1 Proposition If M is M ∗ -projective.CHAPTER 4. if a quotient fuzzy G-module is fuzzy projective with respect to another fuzzy G-module. Also. 4. .3. provided that the G-modules are relatively projective. then ∃ an anti-weak fuzzy homomorphism between the quotient fuzzy G-modules. Proof.

FUZZY PROJECTIVITY ON . Now g : M → M/N and ψ : M → M ∗ are homomorphisms. . . Let M/N . f : M/N → M ∗ /N ∗ be the mapping deﬁned by f (x + N ) = ψ (x) + N ∗ . Then f is a homomorphism. Hence ∃ a homomorphism h : M/N → M ∗ such that h ◦ g = ψ .2 Proposition If M is M ∗ -projective. 92 cal homomorphism. Hence f : M/N → ∴ M/N is M ∗ -projective. Let g : M → M/N be the canonical homomorphism deﬁned by g (x) = x + N . Proof. 4. Also π ◦ h = f .3. x ∈ M . M π g f f ψ φ M∗ π M ∗ /N ∗ π M ∗ /Y ∗ M ∗ /N ∗ can be lifted to h : M/N → M ∗ such that π ◦ h = f . then M/N is M ∗ /N ∗ -projective where N and N ∗ are G-submodules of M and M ∗ respectively. x ∈ M .CHAPTER 4.

93 Since M is M ∗ -projective. y ∈ M ∗. Since M is M ∗ /N ∗ -projective. φ : M → M ∗ /N ∗ can be lifted π : M ∗ /N ∗ → M ∗ /Y ∗ such that π ◦ φ = g where π (y + N ∗ ) = y + Y ∗ . . Since M is M ∗ -projective. . Then f is a homomorphism. Let f : M/N → M ∗ /N ∗ be ping f : M/N → M ∗ /N ∗ . . Hence π ◦ f = f . FUZZY PROJECTIVITY ON . Since M is M ∗ /N ∗ -projective. ψ (x) ∈ M ∗ = ψ (x) + Y ∗ ∈ M ∗ /Y ∗ = f (x + N ) f ◦ π = π ◦ φ. (π ◦ f )(x + N ) = π [f (x + N )] = π [ψ (x) + N ∗ ]. f ◦ π can be lifted to φ such that f ◦ h = φ. Then f is a homomorphism. ∃ by π (x) = x + N . f : M/N → M ∗ /Y ∗ and π : M ∗ /N ∗ → M ∗ /Y ∗ where Y ∗ /N ∗ is a For x + N ∈ M/N . ∃ a map- deﬁned by f (x + N ) = ψ (x) + N ∗ where ψ (x) ∈ M ∗ . Let π be the natural homomorphism from M into M/N deﬁned Y ∗ /N ∗ be a G-submodule of M ∗ /N ∗ . deﬁned by f (x + N ) = ψ (x) + N ∗ such that G-submodule of M ∗ /N ∗ . Since M is M ∗ /N ∗ -projective. x ∈ M .CHAPTER 4. Let M ∗ -projective. M is M ∗ /N ∗ -projective and M/N is to ψ : M → M ∗ such that π ◦ ψ = φ where π : M ∗ → M ∗ /N ∗ . Hence ∃ homomorphisms f : M/N → M ∗ /N ∗ .

5 Proposition If M and M ∗ are relatively projective G-modules then M/N and M ∗ /N ∗ are relatively projective quotient G-modules where N and N ∗ are G-submodules of M and M ∗ respectively and N ∗ = Im(N ). ∴ f can be lifted to f such that π ◦ f = f .3. Hence M ∗ /N ∗ is M/N -projective. .3. 4. . Proof. FUZZY PROJECTIVITY ON . Now M/N is M ∗ /N ∗ -projective and M ∗ /N ∗ is M/N -projective.4 Deﬁnition[45] Two G-modules M and M ∗ are said to be relatively projective if M is M ∗ -projective and M ∗ is M -projective. M ∗ is M -projective. M/N is M ∗ /N ∗ -projective. Hence M/N and M ∗ /N ∗ are relatively projective quotient G-modules. If M is M ∗ -projective.3. 4. by the above proposition. 94 ∴ M/N is M ∗ /N ∗ -projective. .CHAPTER 4. 4. Since M and M ∗ are relatively projective G-modules.3 Deﬁnition [45] A G-module M is said to be self-projective if M is M -projective.

√ √ and so Q( 2) is Q( 3)-projective. . Then M and M ∗ are √ √ G-modules. Deﬁne ψ : Q( 2) → Q( 3) by ψ (a + b 2) = √ a + b 3. b ∈ Q. Also Q is a proper G-submodule of both Q( 2) and Q( 3). Let π be the natural √ √ homomorphism from Q( 3) → Q( 3)/Q.CHAPTER 4. √ √ π (ψ (a + b 2)) = π (a + b 3) √ =b 3+Q √ = φ(a + b 2) ∴ π ◦ ψ = φ. M = Q( 2) and M ∗ = Q( 3). a. √ √ √ √ Hence φ : Q( 2) → Q( 3)/Q can be lifted to ψ : Q( 2) → Q( 3). Then ψ is a homomorphism. . √ √ Consider the quotient G-modules is Q( 2)/Q and Q( 3)/Q. Let φ be √ √ √ the homomorphism deﬁned from Q( 2) → Q( 3)/Q by φ(a + b 2) = √ √ √ √ b 3 + Q. .3. √ √ ∴ π (a + b 3) = (a + b 3) + Q √ = b 3 + Q. b ∈ Q. 4. FUZZY PROJECTIVITY ON . −1}. b ∈ Q. √ √ For a + b 2 ∈ Q( 2).6 Example 95 √ √ Let G = {1. a. √ √ Now to show that Q( 2)/Q is Q( 3)-projective. a.

√ = b 2 + Q. √ Q( 2)/Q √ Q( 3)/Q a. .CHAPTER 4. f (b 2 + Q) = b 3 + Q. √ Q( 2) ψ h π φ π √ Q( 3) 96 f √ √ √ Deﬁne f : Q( 2)/Q → Q( 3)/Q by f ((a + b 2)+ Q) = (a + b 3)+ Q. √ √ For a + b 2 + Q ∈ Q( 2)/Q. . √ √ (π ◦ h)((a + b 2) + Q) = π [h[(a + b 2) + Q]] √ √ π ◦ h(b 2 + Q) = π (a + b 3) √ =b 3+Q √ = f (b 2 + Q). √ √ √ √ i. . That is √ √ π (a + b 2) = (a + b 2) + Q. FUZZY PROJECTIVITY ON ..e. b ∈ R. Let π : Q( 2) → Q( 2)/Q be √ the natural homomorphism. a. b ∈ Q. a. b ∈ Q √ √ √ √ Deﬁne h : Q( 2)/Q → Q( 3) by h((a + b 2)+ Q) = a + b 3.

M = Q( 2) and M ∗ = Q( 3). −1}. Hence Q( 2)/Q is Q( 3)-projective. 4. ∃ a mapping √ √ √ √ f : Q( 2)/Q → Q( 3). . √ √ √ √ Since Q( 2) is Q( 3)/Q-projective.CHAPTER 4. deﬁned by π (a + b 2) = √ √ √ b 2 + Q. b ∈ Q. deﬁned by f (b 2 + Q) = b 3 + Q such that φ π .7 Example 97 √ √ √ Let G = {1. . a. √ √ ∴ π ◦ h = f . FUZZY PROJECTIVITY ON . Since Q( 2) is Q( 3)/Q-projective.3. ∃ π : Q( 3)/Q → Q( 3) such √ √ that π ◦ φ = g where π (b 3 + Q) = b 3. Then Q( 2)/Q is √ Q( 3)/Q-projective √ √ ψ Q( 2) Q( 3) π g √ f Q( 2)/Q f √ Q( 3)/Q π √ Q( 3) √ √ Let Q( 3)/Q(= Y ∗ /N ∗ ) be a G-submodule of Q( 3)/Q(= M ∗ /N ∗ ). Let π be the natu√ √ √ ral homomorphism from Q( 2) → Q( 2)/Q. b ∈ Q.

Since Q( 2) is Q( 3)/Q-projective. b ∈ Q. √ If Y ∗ /N ∗ = Q/Q = Q is the G-submodule of M ∗ /N ∗ = Q( 3)/Q √ √ √ under consideration. For a + b 2 ∈ Q( 2). . √ √ f ◦ π = φ. then π : Q( 3)/Q → Q( 3)/Q/Q/Q = Q( 3)/Q is the identity mapping and hence the result is true. √ √ ∴ π ◦ f = f . . Hence Q( 2)/Q is Q( 3)/Q-projective. FUZZY PROJECTIVITY ON . Then f is a homomorphism. . √ √ (f ◦ π )(a + b 2) = f [π [(a + b 2)] √ = f (b 2 + Q) √ =b 3+Q √ = φ(a + b 2). √ √ Then f is a homomorphism. 98 √ √ √ √ Let f : Q( 2)/Q → Q( 3) be deﬁned by f (b 2 + Q) = b 3. f ◦ π can be lifted to φ such that f ◦ π = π ◦ φ.CHAPTER 4. √ √ (π ◦ f )(b 2 + Q) = π [f (b 2 + Q)] √ = π (b 3 + Q) √ =b 3 √ = f (b 2 + Q).

∀m ∈ M and ψ ∈ Hom(M. such that µ is ν -projective. Then η : M/N → [0. N is a G-submodule of M . . Proof. Since M is M ∗ - M µ ψ ν M∗ π [0. projective. M ∗ ). .CHAPTER 4. 1] η h φ π M ∗ /N ∗ f Now it remains to prove that η (m + N ) ≤ ν (h(m + N )). 4.3. Given that µ is ν -projective. FUZZY PROJECTIVITY ON . deﬁned by η (m + N ) = µ(m). m ∈ M and η is ν -projective. M/N is M ∗ -projective. 1] is a fuzzy G-module on ∴ M is M ∗ -projective and µ(m) ≤ ν (ψ (m)).8 Proposition 99 Let µ and ν be fuzzy G-modules on the G-modules M and M ∗ -respectively M/N . ∀m + N ∈ M/N M/N .

CHAPTER 4. ∀m∗ ∈ M ∗ . ∴ η is ν -projective.3.9 Proposition Let µ and ν be fuzzy G-modules on M and M ∗ such that µ is ν -projective. M ∗ ). ∀m ∈ M and ψ ∈ Hom(M. ∵ π is the canonical homomorphism from M into M/N . . FUZZY PROJECTIVITY ON . For m + N ∈ M/N . Then the fuzzy G-modules η and η ∗ on M/N and M ∗ /N ∗ result deﬁned by η (m + N ) = µ(m). Given that µ is ν -projective ∴ M is M ∗ -projective and µ(m) ≤ ν (ψ (m)). and h : M/N → M ∗ . . η (m + N ) = µ(m) (given) ∵ µ is ν -projective 100 ≤ ν (ψ (m)). Then η is η ∗ -projective. 4. Proof. ∀m ∈ M and η ∗ (m∗ + N ∗ ) = ν (m∗ ). = ν {(h ◦ π )(m)} = ν {h[π (m)]} η (m + N ) ≤ ν {h(m + N )}. .

Then f is a By Proposition 4. M ∗ /N ∗ -projective.2. ∀ m + N ∈ M/N .3. FUZZY PROJECTIVITY ON . we know that M/N is ≤ homomorphism. it remains to prove that η (m + N ) For m + N ∈ M/N . M ∗ /N ∗ ). η (m + N ) = µ(m) ≤ ν (ψ (m)) m∈M = η ∗ (ψ (m) + N ∗ ) = η ∗ (f (m + N )). 1] Deﬁne f : M/N → M ∗ /N ∗ by f (m + N ) = ψ (m) + N ∗ .CHAPTER 4. . . η ∗ (f (m + N )). Now. ψ M 101 M∗ π µ f ν π M/N η f M ∗ /N ∗ η∗ [0. . f ∈ Hom(M/N.

. [0. M = Q( 2) and M ∗ = Q( 3). M ∗ /N ∗ ). √ √ a.3. −1}.CHAPTER 4. a.10 Example √ √ √ Let G = {1. 1] µ ν √ Q( 2) ψ √ Q( 3) π √ Q( 3)/Q φ . FUZZY PROJECTIVITY ON . √ √ ∴ Q( 2) is Q( 3)-projective. . such that π ◦ ψ = φ. m+N ∈ M/N and f ∈ Hom(M/N. ∴ η is η ∗ -projective. 4. b ∈ Q. Then φ can be lifted to ψ : Q( 2) → √ √ √ Q( 3) given by ψ (a + b 2) = a + b 3. 102 ∴ η (m+N ) ≤ η ∗ (f (m+N )). Let φ : Q( 2) → √ √ √ Q( 3)/Q be the homomorphism deﬁned by φ(a + b 2) = (a + b 3)+ Q. b ∈ Q and π : Q( 3) → Q( 3)/Q be the canonical homomorphism so √ √ √ that π (a + b 3) = (a + b 3) + Q.

1] by ∴ µ is ν -projective.6. if a = 0. b = 0      1/6. √ Now. M = Q( 2). 1] by    1/4. by example 4. Let h : Q( 2)/Q → Q( 3) be the mapping √ √ √ h((a + b 2) + Q) = ψ (a + b 2) = a + b 3. deﬁne µ : Q( 2) → [0. b ∈ Q.3. d = 0     1/3. if c = d = 0    √ ν (c + d 3) = 1/2.11 Example √ √ Let G = {1. if b = 0    1. if c = 0. 103 √ and ν : Q( 3) → [0. . . Q( 2)/Q is Q( 3)√ √ projective. Deﬁne η on Q( 2)/Q by √ √ η ((a + b 2) + Q) = µ(a + b 2). Deﬁne µ and ν on M and √ M ∗ as in the above example.CHAPTER 4. FUZZY PROJECTIVITY ON . if d = 0. if a = b = 0    √ µ(a + b 2) = 1/5. M ∗ = Q( 3). .3. 4. −1}. a. √ √ √ √ Since Q( 2) is Q( 3)-projective.

b ∈ Q. 4. −1}. Now. M = Q( 2). √ √ µ(a + b 2) ≤ ν (ψ (a + b 2)). √ √ η ((a + b 2) + Q) = µ(a + b 2) √ ≤ ν (ψ (a + b 2)). a. . Deﬁne η : Q( 2)/Q → [0. 1] by √ √ √ η ((a + b 2) + Q) = µ(a + b 2) and η ∗ : Q( 3)/Q → [0.CHAPTER 4. 1] by √ √ η ∗ ((a + b 3) + Q) = ν (a + b 3). Since µ is ν -projective. √ √ For (a + b 2) + Q ∈ Q( 2)/Q.12 Example √ √ Let G = {1. M ∗ ).3. Let µ and ν be fuzzy G-modules on M and M ∗ as deﬁned in the above example. ∵ µ is ν -projective √ = ν {(h ◦ π )(a + b 2)} √ = ν {h[π (a + b 2)]} √ ≤ ν {h(a + b 2) + Q)} ∴ η is ν -projective. M ∗ = Q( 3). . it remains to prove that √ √ η ((a + b 2) + Q) ≤ ν (h(a + b 2) + Q). FUZZY PROJECTIVITY ON . 104 √ √ Let π : Q( 2) → Q( 2)/Q be the canonical homomorphism deﬁned by √ √ π (a + b 2) = (a + b 2 + Q. ∀ ψ ∈ Hom(M. Then µ is √ ν -projective. .

√ √ For (a + b 2) + Q ∈ Q 2/Q. Now. we know that Q( 2)/Q is √ √ Q( 3)/Q-projective.7. . In a similar manner. . we can say that f is an anti-weak fuzzy homomorphism of η ∗ onto η .13 Remark It may be recalled that when µ is ν -projective. √ Then f is a homomorphism. since η is η ∗ -projective. ∴ η is ν -projective. By example 4. ψ −1 is an anti-weak fuzzy homomorphism of ν and µ.3.CHAPTER 4. FUZZY PROJECTIVITY ON . √ √ η ((a + b 2) + Q) = µ(a + b 2) √ ≤ ν (ψ (a + b 2)). ∵ µ is ν -projective √ = η ∗ (ψ (a + b 2) + Q) √ = η ∗ (f ((a + b 2) + Q)) √ √ η ((a + b 2) + Q) ≤ ν ∗ (f ((a + b 2) + Q)). . 105 √ √ √ √ Deﬁne f : Q( 2)/Q → Q( 3)/Q by f ((a + b 2)+ Q) = (a + b 3)+ Q. it remains to prove that η ((a + b 2) + Q) ≤ √ η ∗ (f ((a + b 2) + Q)).3. 4.